The Virtual Element Method for the Dam Foundation With Joint - Sun, Yinghao; Sun, Guanhua; Yi, Qi; Wang, Jiao (Frontiers in Earth Science, 2022)
The contact is a typical non-linear problem which exists in various projects. For traditional three-node triangular elements and four-node quadrilateral elements, the accuracy and convergence of the calculation results are affected by the quality of the mesh. The test space and trial space in the virtual element method (VEM) do not need to be accurately calculated, avoiding mesh dependence. In this paper, the formulation of linear elasticity and the formulation of the frictionless node-to-segment (NTS) contact model via VEM are shown. There are four numerical simulations. The first numerical example studies the sensitivity of the virtual element method to mesh distortion by comparing with the finite element results. The accuracy and convergence of algorithm is investigated by the second numerical example. The second and third numerical examples simultaneously study the effect of the penalty factor on the results. In the third example, the effect of mesh shape and number of Voronoi mesh elements on the results was investigated by comparing normal contact stresses. The fourth numerical example studies the application of the method to engineering.